1998
DOI: 10.1093/jn/128.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Increases in the Concentrations of Available Iron in Response to Dietary Iron Supplementation Are Associated with Changes in Crypt Cell Proliferation in Rat Large Intestine , ,

Abstract: High concentrations of iron in the diet have been shown to increase chemically induced colorectal tumors in rats. It is therefore important to understand the influence of dietary iron on the concentration of unabsorbed iron in the large intestine and its distribution between soluble and insoluble pools in the luminal compartment. We sought to investigate this issue and to establish whether iron modifies mucosal cell proliferation, which is thought to influence initiation and progression through the adenoma car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 15 publications
3
64
0
Order By: Relevance
“…It has been suggested that chronic iron intake can affect intestinal homeostasis by altering intestinal microbial composition, oxidative stress, inflammation, etc. [13,15,16,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that chronic iron intake can affect intestinal homeostasis by altering intestinal microbial composition, oxidative stress, inflammation, etc. [13,15,16,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…3,18 Furthermore, tumor cells have a greater ability than normal cells to grow and survive in the presence of high concentrations of iron 19 ; when iron is deficient, the rate of tumor growth actually decreases. 20 There are two distinct routes of exposure to iron.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that fractional intestinal Fe absorption is frequently low, with minor variations depending on the food matrix or the physiological state, unabsorbed Fe in the small intestine reaches the large intestine in an "available" form within the range required for significant free radical production (8)(9)(10). These effects would impact (a) the mucosal barrier integrity by affecting the cellular dynamics and permeability in intestinal mucosa, as well as (b) the microbial composition and metabolic activity by stimulating the growth and pathogenicity of intestinal bacteria (9,(26)(27)(28).…”
Section: 23 25)mentioning
confidence: 99%
“…Interestingly, only at this time point were these effects significantly associated with liver Fe stores, suggesting that increased liver Fe accumulation could have occurred as morphological changes took place in the intestine. Crypt hyperplasia in the large intestine has been shown in rodent studies after Fe supplementation, such as inorganic salts (9) or heme Fe (27), and could occur as a compensatory response to injury induced by excess Fe in the intestinal lumen (27). Although we used a dietary Fe loading at approximately 10 times the recommended levels for rodents (14), other authors have reported changes in crypt cellularity and lipid peroxidation with milder dietary Fe contents (approximately 100 mg Fe/kg diet) but with longer experiments (.6 mo) (9,10).…”
Section: 23 25)mentioning
confidence: 99%